Preparation method of spherical hard carbon negative electrode material suitable for sodium ion battery

The spherical hard carbon negative electrode material was prepared by co-pyrolytic solution of metal acetate salt and starch, combined with spray drying, low-temperature carbonization and high-temperature calcining steps, solving the problem of starch expansion and melting during the pyrolytic solution, and significantly improving the energy storage capacity and circulation stability.

CN119797331AInactive Publication Date: 2025-04-11SOUTHWEAT UNIV OF SCI & TECH

Patent Information

Application Number
CN202510079670.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the process of pyrolytic conversion of starch to hard carbon, the energy storage capacity and circulation stability are insufficient due to expansion and melting, resulting in the problems of reversible capacity and low Coulomb efficiency.

Method used

The method of co-pyrolyzing of metal acetate salt and starch is adopted to produce metal oxides by thermal decomposition of metal acetate salt, filling the pores of starch molecules, achieving a closed-cell effect, inhibiting starch foaming, and preparing spherical hard carbon negative electrode materials through spray drying, low-temperature carbonization and high-temperature calcination.

Benefits of technology

Effectively inhibit starch foaming, maintain a spherical structure, significantly improve the energy storage capacity and circulation stability of hard carbon materials, and improve the reversible specific capacity and first-time Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797331A_ABST
    Figure CN119797331A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a spherical hard carbon negative electrode material suitable for a sodium ion battery, and relates to the technical field of electrode materials, the preparation method comprises the following steps: (1) mixing acetic acid metal salt and a first acid solution in an aqueous solution, and stirring until the solution is transparent; (2) sequentially adding starch and a second acid solution into the transparent solution, and heating and stirring until uniformly dispersed suspension slurry is obtained; (3) carrying out spray drying on the suspension slurry to obtain uniformly mixed starch / acetic acid metal salt powder; (4) performing carbonization treatment, washing and drying on the powder in sequence to obtain a hard carbon precursor; and (5) calcining the hard carbon precursor to obtain the spherical hard carbon negative electrode material. By adopting an acetic acid metal salt co-pyrolysis method, foaming of the starch in the pyrolysis process can be inhibited, the original form and structural integrity of the material are kept, more closed pore volumes are shown, and the energy storage capacity and the cycling stability of the hard carbon material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery. Background Art

[0002] As an amorphous carbon material, hard carbon (HC) is usually composed of a large number of disordered graphite crystallites and amorphous regions. Hard carbon has a slope region greater than 0.1V and a low voltage platform region less than 0.1V, which can provide significant capacity. Therefore, it has received great attention in the field of ion batteries.

[0003] Among ion batteries, sodium-ion batteries have gradually become the focus of research due to their significant advantages in terms of resource abundance, cost-effectiveness, safety, power performance, and low-temperature performance. For sodium-ion batteries, the current sodium storage mechanism is adsorption-intercalation-pore filling, and the specific sodium storage behavior of hard carbon is mainly manifested in: 1) adsorption of surface defect sites and oxygen-containing functional groups; 2) intercalation of graphite sheets; 3) filling of closed pores. Therefore, these three sodium storage methods can be selected for regulation to obtain high-performance hard carbon to meet the application of sodium-ion batteries.

[0004] However, it is difficult to confirm whether the regulation of surface defect sites and oxygen-containing functional groups is reversible for the adsorption of sodium ions, because some defects and functional groups CO will cause irreversible capacity loss, which will lead to a decrease in the initial coulombic efficiency. For intercalation, due to the small capacity occupied, the coulombic efficiency is also difficult to be effectively improved. For closed-pore filling, since abundant closed pores can be used for reversible storage of sodium ions, the capacity can be greatly increased. Therefore, in terms of sodium storage, choosing closed-pore filling is also the most effective means of regulation at present.

[0005] As the second largest renewable resource on earth, starch has become the focus of hard carbon material preparation research because of its pure, low-cost, and natural spherical structure. However, in the process of starch conversion to hard carbon, due to the expansion and melting problems, the hard carbon obtained by direct pyrolysis usually shows a lamellar structure in the electron microscope (SEM). Not only is the specific surface area too large, but the tap density is also extremely low, making it difficult to form abundant closed pores. Therefore, the sodium storage performance is greatly limited, and it is difficult to provide a high reversible capacity and coulombic efficiency.

[0006] In summary, how to effectively combine starch with closed-cell regulation to achieve the conversion of starch into hard carbon while maintaining a high energy storage capacity and good cycle stability has become one of the main technical problems that technicians in this field urgently need to solve. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery, which can solve the problem of insufficient energy storage capacity and cycle stability due to expansion and melting during the pyrolysis conversion of starch into hard carbon, thereby causing low reversible capacity and coulombic efficiency.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery comprises the following steps:

[0010] (1) mixing a metal acetate and a first acidic solution in an aqueous solution and stirring until the solution becomes transparent; the volume ratio of the first acidic solution to the aqueous solution is 1:100-250;

[0011] (2) adding starch and a second acidic solution to the transparent solution obtained in step (1) in sequence, and heating and stirring until a uniformly dispersed suspension slurry is obtained; the mass ratio of the starch to the metal acetate is 5 to 0.5:1; the volume ratio of the second acidic solution to the first acidic solution is 1 to 5:1; and the solid content of the slurry is 10 wt% to 50 wt%;

[0012] (3) spray drying the suspension slurry obtained in step (2) to obtain a uniformly mixed starch / acetic acid metal salt powder;

[0013] (4) sequentially carbonizing, washing, and drying the starch / metal acetate powder to obtain a hard carbon precursor;

[0014] (5) The hard carbon precursor is calcined to obtain a spherical hard carbon negative electrode material.

[0015] Preferably, the metal acetate is any one of copper acetate, zinc acetate, magnesium acetate, calcium acetate, aluminum acetate and manganese acetate.

[0016] Preferably, the starch is any one of corn starch, mung bean starch, potato starch, wheat starch, tapioca starch, lotus root starch and glutinous rice starch.

[0017] Preferably, the first acidic solution is any one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid and phosphoric acid, and the concentration is 0.5 to 3 mol / L.

[0018] Preferably, the second acidic solution is any one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid and phosphoric acid, and the concentration is 0.5-1 mol / L.

[0019] Specifically, in step (2), the heating temperature is 60 to 90° C., and the stirring speed is 20 to 100 r / min.

[0020] Specifically, in step (3), the spray drying conditions are set as follows: fan frequency 10-60 Hz, feed rate 10-2000 mL / h, air inlet temperature 100-275°C, and air outlet temperature 60-150°C.

[0021] Specifically, the step (4) comprises the following steps:

[0022] (401) In an oxygen-free atmosphere, the starch / acetic acid metal salt powder is subjected to a low-temperature carbonization treatment, wherein the treatment conditions are: heating to 400-800°C at a heating rate of 1-5°C / min, and pre-calcining for 0.5-6h; the oxygen-free atmosphere can be any one of nitrogen, argon, and a mixture of argon and hydrogen;

[0023] (402) cooling the product after the low-temperature carbonization treatment to room temperature, and then washing it with a third acidic solution and water in sequence;

[0024] (403) The washed product is dried to obtain a hard carbon precursor.

[0025] Preferably, the third acidic solution is any one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid, and the concentration is 1 mol / L.

[0026] Furthermore, the step (5) is specifically as follows: in an inert atmosphere, the temperature is raised to 1100-1600° C. at a heating rate of 1-5° C. / min, and the hard carbon precursor is calcined for 1-6 hours to obtain a spherical hard carbon negative electrode material. The inert atmosphere can be any one of nitrogen and argon.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] (1) The present invention uses metal acetate as a key medium. By co-pyrolysis of metal acetate and starch, the metal acetate is thermally decomposed to produce metal oxides, which are filled in the pores of starch molecules, achieving a pore-forming and pore-closing effect, thereby inhibiting the foaming of starch during the pyrolysis process, solving the common expansion and melting problems of starch during the pyrolysis process, and effectively maintaining its original spherical structure, providing a basis for the subsequent acquisition of spherical hard carbon.

[0029] This unique control method maintains the ideal microscopic morphology (spherical structure) of the hard carbon material. At the same time, due to the realization of the closed-cell effect, the present invention only needs to use low-temperature carbonization technology to obtain the hard carbon precursor, which is not only simple to operate, but also saves energy consumption.

[0030] (2) The present invention adds a first acidic solution and a second acidic solution respectively during the process of preparing the hard carbon material. On the one hand, the acidic solution can accelerate the decomposition and uniform dispersion of starch molecules in the solution; on the other hand, the addition of the acidic solution can also avoid a large amount of hydrolysis of the metal acetate in the solution, retaining the integrity of the metal acetate, so that it can participate in the thermal decomposition as much as possible to produce metal oxides. In this way, it also provides a good guarantee for the metal acetate to inhibit the foaming of starch during the thermal decomposition process. Therefore, the present invention obtains an unexpected technical effect by adding a small amount of acidic solution.

[0031] (3) After obtaining the hard carbon precursor through low-temperature carbonization treatment, the present invention uses a third acidic solution to wash the product, which can better remove metal oxides and achieve open pores after closed pores. Finally, the final hard carbon material is obtained through high-temperature calcination. This also provides a guarantee for the hard carbon material to achieve good sodium storage function.

[0032] (4) The present invention has reasonable raw material selection, ingenious preparation process and low preparation cost, which not only solves the problem of biomass hard carbon morphology and particle size, but also has a wide source of raw materials and a simple overall preparation process, which is conducive to mass production. Moreover, when the hard carbon material prepared by the present invention is applied to ion batteries, especially sodium ion batteries, it can greatly improve the platform area capacity, show extremely high reversible capacity and very high first coulomb efficiency. Therefore, the present invention is very suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM image of the hard carbon negative electrode material prepared in Example 1 of the present invention.

[0034] Figure 2 This is a charge and discharge curve diagram of the hard carbon negative electrode material prepared in Example 1 of the present invention.

[0035] Figure 3 This is the SEM image of the hard carbon negative electrode material prepared in the comparative example.

[0036] Figure 4 It is the charge and discharge curve diagram of the hard carbon negative electrode material prepared in the comparative example. DETAILED DESCRIPTION

[0037] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with various embodiments.

[0038] Example 1

[0039] This embodiment provides a spherical hard carbon material, which can be used as a negative electrode material for an ion battery (such as a lithium ion battery, a sodium ion battery), and provides a significant reversible capacity for the battery. The preparation of the spherical hard carbon negative electrode material mainly includes five stages: preparing an aqueous solution of an acetic acid metal salt, co-pyrolyzing the acetic acid metal salt and starch, spray drying, powder carbonization, and high-temperature calcination. The five stages are introduced below.

[0040] 1. Preparation of Acetic Acid Metal Salt Aqueous Solution

[0041] Weigh 25 g of zinc acetate dihydrate and 2 mL of acetic acid (concentration of 3 mol / L) respectively, add them to 500 mL of deionized water, and continue stirring at room temperature until they are completely dissolved and transparent to obtain an aqueous solution of zinc acetate dihydrate.

[0042] 2. Co-pyrolysis of metal acetate and starch

[0043] 100 g of corn starch was added to the aqueous solution of zinc acetate dihydrate and 10 mL of acetic acid (concentration of 3 mol / L) was added dropwise, and then stirred at 90° C. for 0.5 h at a stirring speed of 100 r / min to obtain a suspension slurry with a solid content of 25 wt% and uniform dispersion.

[0044] 3. Spray Drying

[0045] The slurry was spray dried under the following conditions: fan frequency 50 Hz, feed rate 360 ​​mL / h, air inlet temperature 110° C., air outlet temperature 80° C., to obtain a uniformly mixed starch / metal acetate powder.

[0046] 4. Powder Carbonization

[0047] The starch / metal acetate powder was pre-calcined at 600°C for 2 h in an Ar atmosphere at a heating rate of 2°C / min, and then cooled to room temperature. Thereafter, the pre-calcined product was washed with 1 mol / L nitric acid and water in turn, and dried in an oven at 60°C for 6 h to obtain a hard carbon precursor.

[0048] 5. High temperature calcination

[0049] The hard carbon precursor was placed in a N2 atmosphere and calcined at 1500°C for 3 hours at a heating rate of 2°C / min to obtain a spherical hard carbon material.

[0050] Morphological observations and conclusions:

[0051] The spherical hard carbon negative electrode material prepared in this embodiment has a scanning electron microscope (SEM) image as shown in FIG. Figure 1As shown in the figure, it can be seen that the prepared hard carbon sample shows effective suppression of starch foaming and melting, allowing it to maintain its original spherical structure. This result shows that the original morphology and structural integrity of the material are maintained by optimizing the preparation process and adding metal acetate as an additive.

[0052] Performance test results:

[0053] The prepared hard carbon material, carbon black and polyvinylidene fluoride were used to prepare electrode sheets in a mass ratio of 8:1:1, and then assembled into CR2032 button batteries. After testing, the specific capacity is as follows Figure 2 As shown, the current density of the hard carbon negative electrode material is 20 mA / g, the reversible specific capacity is 369.17 mAh / g, and the first coulombic efficiency is 84.68%.

[0054] Example 2

[0055] The difference from Example 1 is that the process of preparing the hard carbon negative electrode material in this example is as follows:

[0056] (1) Weigh 30 g of copper acetate and 5 mL of hydrochloric acid (concentration of 1 mol / L) respectively, add 500 mL of deionized water, and continue stirring at room temperature until completely dissolved and transparent. Then, add 100 g of wheat starch to the solution and drop 5 mL of hydrochloric acid (concentration of 1 mol / L), heat and continue stirring for 1 h (heating temperature of 80° C., stirring speed of 70 r / min), and obtain a suspension slurry with a solid content of 26 wt% and uniform dispersion;

[0057] (2) spray drying the suspended slurry at a fan frequency of 50 Hz, a feed rate of 360 mL / h, an air inlet temperature of 110° C., and an air outlet temperature of 80° C. to obtain a uniformly mixed starch / acetic acid metal salt powder;

[0058] (3) pre-calcining the starch / acetic acid metal salt powder at 500°C for 3 h at a heating rate of 3°C / min under an Ar atmosphere, and then washing the cooled product with 1 mol / L sulfuric acid and water in turn, and drying it in an oven at 80°C for 8 h to obtain a hard carbon precursor;

[0059] (4) The hard carbon precursor is placed in a N2 atmosphere and calcined at 1600°C for 2 h at a heating rate of 2°C / min to obtain the spherical hard carbon material of this embodiment.

[0060] Morphological observations and conclusions:

[0061] The spherical hard carbon negative electrode material prepared in this example also maintains the original morphology and structural integrity of the material.

[0062] Performance test results:

[0063] The prepared hard carbon material, carbon black and polyvinylidene fluoride were prepared into electrode sheets in a mass ratio of 8:1:1, and then assembled into CR2032 button batteries. After testing, the current density of the hard carbon negative electrode was 20mA / g, the reversible specific capacity was 340.16mAh / g, and the first coulombic efficiency was 80.52%.

[0064] Example 3

[0065] The difference from Example 1 is that the process of preparing the hard carbon negative electrode material in this example is as follows:

[0066] (1) Weigh 40 g of calcium acetate and 5 mL of phosphoric acid (concentration of 1 mol / L) respectively, add 500 mL of deionized water, and continue stirring at room temperature until completely dissolved and transparent. Then, add 100 g of wheat starch and drop 5 mL of phosphoric acid (concentration of 1 mol / L) to the solution, and heat and continue stirring for 0.5 h (heating temperature is 80° C., stirring speed is 20 r / min) to obtain a suspension slurry with a solid content of 28 wt% and uniform dispersion;

[0067] (2) spray drying the suspended slurry at a fan frequency of 50 Hz, a feed rate of 360 mL / h, an air inlet temperature of 120° C., and an air outlet temperature of 85° C. to obtain a uniformly mixed starch / acetic acid metal salt powder;

[0068] (3) pre-calcining the starch / metal acetate powder at 550°C for 3 h at a heating rate of 1°C / min under an Ar atmosphere, and then washing the cooled product with 1 mol / L sulfuric acid and water in turn, and drying it in an oven at 90°C for 3 h to obtain a hard carbon precursor;

[0069] (4) The hard carbon precursor is placed in a N2 atmosphere and calcined at 1400°C for 2 h at a heating rate of 2°C / min to obtain the spherical hard carbon material of this embodiment.

[0070] Morphological observations and conclusions:

[0071] The spherical hard carbon negative electrode material prepared in this example also maintains the original morphology and structural integrity of the material.

[0072] Performance test results:

[0073] The prepared hard carbon material, carbon black and polyvinylidene fluoride were prepared into electrode sheets in a mass ratio of 8:1:1, and then assembled into CR2032 button batteries. After testing, the current density of the hard carbon negative electrode was 20mA / g, the reversible specific capacity was 330.18mAh / g, and the first coulomb efficiency was 79.88%.

[0074] Example 4

[0075] The difference from Example 1 is that the process of preparing the hard carbon negative electrode material in this example is as follows:

[0076] (1) Weigh 40 g of magnesium acetate and 5 mL of acetic acid (concentration of 3 mol / L) respectively, add 500 mL of deionized water, and continue stirring at room temperature until completely dissolved and transparent. Then, add 100 g of wheat starch to the solution and drop 5 mL of acetic acid (concentration of 3 mol / L), heat and continue stirring for 0.5 h (heating temperature is 70°C, stirring speed is 40 r / min), and obtain a suspension slurry with a solid content of 28 wt% and uniform dispersion.

[0077] (2) spray drying the suspended slurry at a fan frequency of 50 Hz, a feed rate of 360 mL / h, an air inlet temperature of 120° C., and an air outlet temperature of 85° C. to obtain a uniformly mixed starch / acetic acid metal salt powder;

[0078] (3) pre-calcining the starch / acetic acid metal salt powder at 600°C for 3 h at a heating rate of 2°C / min under an Ar atmosphere, and then washing the cooled product with 1 mol / L acetic acid and water in turn, and drying it in an oven at 70°C for 5 h to obtain a hard carbon precursor;

[0079] (4) The hard carbon precursor is placed in a N2 atmosphere and calcined at 1500°C for 2 h at a heating rate of 2°C / min to obtain the spherical hard carbon material of this embodiment.

[0080] Morphological observations and conclusions:

[0081] The spherical hard carbon negative electrode material prepared in this example also maintains the original morphology and structural integrity of the material.

[0082] Performance test results:

[0083] The prepared hard carbon material, carbon black and polyvinylidene fluoride were prepared into electrode sheets in a mass ratio of 8:1:1, and then assembled into CR2032 button batteries. After testing, the current density of the hard carbon negative electrode was 20mA / g, the reversible specific capacity was 380.16mAh / g, and the first coulomb efficiency was 82.38%.

[0084] Example 5

[0085] The difference from Example 1 is that the process of preparing the hard carbon negative electrode material in this example is as follows:

[0086] (1) Weigh 40 g of aluminum acetate and 5 mL of acetic acid (concentration of 2 mol / L) respectively, add 500 mL of deionized water, and continue stirring at room temperature until completely dissolved and transparent. Then, add 100 g of soluble starch to the solution and drop 5 mL of acetic acid (concentration of 2 mol / L), heat and continue stirring for 0.5 h (heating temperature of 80° C., stirring speed of 80 r / min), and obtain a suspension slurry with a solid content of 28 wt% and uniform dispersion;

[0087] (2) spray drying the suspended slurry at a fan frequency of 50 Hz, a feed rate of 360 mL / h, an air inlet temperature of 110° C., and an air outlet temperature of 75° C. to obtain a uniformly mixed starch / acetic acid metal salt powder;

[0088] (3) pre-calcining the starch / metal acetate powder at 600°C for 2 h at a heating rate of 5°C / min under an Ar atmosphere, and then washing the cooled product with 1 mol / L hydrochloric acid and water in turn, and drying it in an oven at 50°C for 5 h to obtain a hard carbon precursor;

[0089] (4) The hard carbon precursor was placed in a N2 atmosphere and calcined at 1300°C for 4 h at a heating rate of 2°C / min to obtain the spherical hard carbon material of this embodiment.

[0090] Morphological observations and conclusions:

[0091] The spherical hard carbon negative electrode material prepared in this example also maintains the original morphology and structural integrity of the material.

[0092] Performance test results:

[0093] The prepared hard carbon material, carbon black and polyvinylidene fluoride were prepared into electrode sheets in a mass ratio of 8:1:1, and then assembled into CR2032 button batteries. After testing, the current density of the hard carbon negative electrode was 20mA / g, the reversible specific capacity was 370.16mAh / g, and the first coulombic efficiency was 81.35%.

[0094] Comparative Example

[0095] This comparative example is a solution for preparing starch-based hard carbon material without adding metal acetate, and its preparation process is as follows:

[0096] (1) Add 100 g corn starch to deionized water, heat and continue stirring for 0.5 h (heating temperature is 70° C., stirring speed is 60 r / min), and obtain a suspension slurry with a solid content of 25 wt %.

[0097] (2) spray drying the suspension slurry at a fan frequency of 50 Hz, a feed rate of 360 mL / h, an inlet air temperature of 110° C., and an outlet air temperature of 80° C., and collecting the dried precursor powder;

[0098] (3) placing the precursor powder in an Ar atmosphere and pre-sintering at 600°C for 2 h at a heating rate of 2°C / min to obtain a hard carbon precursor;

[0099] (4) The hard carbon precursor was placed in a N2 atmosphere and calcined at 1500°C for 3 h at a heating rate of 2°C / min to obtain a comparative hard carbon material.

[0100] Morphological observations and conclusions:

[0101] The hard carbon material prepared in the comparative example has a scanning electron microscope image as shown in FIG. Figure 3 As shown in the figure, it can be seen that the hard carbon sample prepared in the comparative example shows starch foaming and melting, and its microscopic morphology is a lamellar structure. This result shows that the original morphology and structural integrity of the material are destroyed during the process of starch pyrolysis and conversion to hard carbon.

[0102] Performance test results:

[0103] The prepared hard carbon material, carbon black and polyvinylidene fluoride were used to prepare electrode sheets in a mass ratio of 8:1:1, and then assembled into CR2032 button batteries. After testing, the specific capacity is as follows Figure 4 As shown, the current density of the hard carbon negative electrode is 20 mA / g, the reversible specific capacity is 250 mAh / g, and the first coulombic efficiency is 64.68%.

[0104] According to the test results of Examples 1-5 and Comparative Examples, the following conclusions can be drawn:

[0105] The present invention adopts a method of co-pyrolysis of metal acetate and starch, which can inhibit the foaming of starch during the pyrolysis process, so that a spherical hard carbon negative electrode material is obtained. Not only the original form and structural integrity of the material are maintained, but also more closed-pore volume is exhibited, which significantly improves the energy storage capacity and cycle stability of the hard carbon material. The reversible specific capacity and first coulombic efficiency are significantly improved, which also provides a very good guarantee for the conversion of starch into hard carbon and its efficient application in negative electrode materials for ion batteries.

[0106] Therefore, compared with the prior art, the present invention has obvious technical progress, outstanding substantive features and remarkable progress.

[0107] The above-mentioned embodiments only express the specific implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the protection scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery, characterized in that: The following steps are involved: (1) mixing a metal acetate and a first acidic solution in an aqueous solution and stirring until the solution becomes transparent; the volume ratio of the first acidic solution to the aqueous solution is 1:100-250; (2) adding starch and a second acidic solution to the transparent solution obtained in step (1) in sequence, and heating and stirring until a uniformly dispersed suspension slurry is obtained; the mass ratio of the starch to the metal acetate is 5 to 0.5:1; the volume ratio of the second acidic solution to the first acidic solution is 1 to 5:1; and the solid content of the slurry is 10 wt% to 50 wt%; (3) spray drying the suspension slurry obtained in step (2) to obtain a uniformly mixed starch / acetic acid metal salt powder; (4) sequentially carbonizing, washing, and drying the starch / metal acetate powder to obtain a hard carbon precursor; (5) The hard carbon precursor is calcined to obtain a spherical hard carbon negative electrode material.

2. The method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery according to claim 1, characterized in that: The metal acetate is any one of copper acetate, zinc acetate, magnesium acetate, calcium acetate, aluminum acetate and manganese acetate.

3. The method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery according to claim 2, characterized in that: The starch is any one of corn starch, mung bean starch, potato starch, wheat starch, cassava starch, lotus root starch and glutinous rice starch.

4. The method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery according to claim 3, characterized in that: The first acidic solution is any one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid and phosphoric acid, and the concentration is 0.5-3 mol / L.

5. The method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery according to claim 4, characterized in that: The second acidic solution is any one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid, and the concentration is 0.5 to 1 mol / L.

6. A method for preparing a spherical hard carbon negative electrode material suitable for sodium ion batteries according to any one of claims 1 to 5, characterized in that: In the step (2), the heating temperature is 60 to 90° C. and the stirring speed is 20 to 100 r / min.

7. The method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery according to claim 6, characterized in that: In the step (3), the spray drying conditions are set as follows: fan frequency 10-60 Hz, feed rate 10-2000 mL / h, air inlet temperature 100-275° C., and air outlet temperature 60-150° C.

8. A method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery according to claim 1 or 2 or 3 or 4 or 5 or 7, characterized in that: The step (4) comprises the following steps: (401) In an oxygen-free atmosphere, the starch / metal acetate powder was subjected to a low-temperature carbonization treatment. The treatment conditions were: heating to 400-800 °C at a heating rate of 1-5 °C / min and pre-calcining for 0.5-6 h; (402) cooling the product after the low-temperature carbonization treatment to room temperature, and then washing it with a third acidic solution and water in sequence; (403) The washed product is dried to obtain a hard carbon precursor.

9. The method for preparing a spherical hard carbon negative electrode material suitable for a sodium ion battery according to claim 8, characterized in that: The third acidic solution is any one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and phosphoric acid, and the concentration is 1 mol / L.

10. The method for preparing a spherical hard carbon negative electrode material suitable for sodium ion batteries according to claim 9, characterized in that: The step (5) is specifically as follows: in an inert atmosphere, the temperature is raised to 1100-1600° C. at a heating rate of 1-5° C. / min, and the hard carbon precursor is calcined for 1-6 hours to obtain a spherical hard carbon negative electrode material.

Citation Information

Patent Citations

  • Sodium-ion battery hard carbon negative electrode material with ultralow specific surface area and preparation method of sodium-ion battery hard carbon negative electrode material

    CN115207350A

  • Preparation method and application of hard carbon microsphere material

    CN115215321A

  • Method for improving performance of starch-based hard carbon negative electrode of battery, prepared negative electrode material and application

    CN115939378A

  • Graphite-silicon composite anode electrode material, a preparation method therefor and an application thereof

    US20240158238A1

  • Near-spherical silicon-carbon negative electrode material, and preparation method therefor and use thereof

    WO2024187562A1

Cited By

  • High-capacity hard carbon material and preparation method and application thereof

    CN120589731A